Bridges of Altantropa Workshop - Antoniou, Klitsa (My University, 2026)
Bridges of Altantropa Workshop, Cyprus University of Technology, Cyprus. Organized in the frame of Malta Pavilion at Venice Art Biennale. Sponsored by the Bank of Valletta and supported by the Malta Arts Council.